The Increasing of Self Efficacy-Self Care on Patients with DM Type 2 Through Peer Group Education Support System - Novira Egan Cahyaningrum; Baiq Nurainun Apriani Idris; Elisa Oktaviana; Hapipah Hapipah; Irwan Hadi (Universitas Muhammadiyah Semarang, 2023)
Diabetes mellitus is still a scourge of the world, DM cases are always increasing every year. Diabetes is a serious chronic disease that occurs when the pancreas does not produce enough insulin, or when the body cannot effectively use the insulin it does produce. Self-efficacy is the patient's self-confidence in his ability to perform self-care. Self-care is an action to help control blood sugar which can produce better health conditions. The risk of complications for people with DM can be reduced by increasing self-efficacy and good self-care. The strategy used to increase self-efficacy_ self-care is through a peer group education support system. This research was conducted to determine the increase in self-efficacy - self-care in patients with type 2 DM through a peer group education support system in the thunderstorm environment. This research is a pre-experimental study with a One Group – Pretest-Posttest without control group design. The population in this study amounted to 20 respondents. The sampling technique in this study was purposive sampling, with a total sample of 18 respondents. The statistical test used in this study was the Wilcoxon sign-rank test. The results of the Wilcoxon sign-rank test obtained a p-value of 0.000 (α=0.05). With good self-efficacy as many as 17 respondents (94.4%) and good self-care as many as 17 respondents (94.4%). So it can be concluded that the peer group education support system has an effect on self-efficacy_self-care for type 2 DM patients in the Geguntur Environment.